ANALISIS STABILITAS LERENG DENGAN PERKUATAN TIANG MENGGUNAKAN METODE ELEMEN HINGGA (STUDI KASUS JALAN DIPONEGORO KM. 2 PASIR PENGARAIAN) - Yarvis Syahwaner; M. Yusa; Syawal Satibi (Aptek, 2019)
The slope that often occurs on the road Diponegoro Km. 2 Pasir Pengaraian has always been a problem by Dinas Bina MargaDan Pengaira Kabupaten Rokan Hulu, but previously improvements were made but were not entirely successful. Then theslope repair with retaining walls using the bore pile pile foundation was considered quite successful to prevent landslides onthe road section. Based on these conditions the author tries to analyze and evaluate the stability of the slope by strengtheningthe bore pile pile, by analyzing the influence of the pile position (Xp/X), pile diameter, pile length (Lz/L) pile and pile spacing(S/D) on the slope. The object of the research was carried out on the slope of Diponegoro Km. 2 Pasir Pengaraian. Theanalysis used is field tension analysis with finite element method analysis of strength reduction. Soil parameters are knownfrom several tests in the field and laboratories which are used as design variables in the analysis process.This thesis presentsthe safety factor of the two-dimensional finite element method with strength reduction analysis using the OPTUMG2 programto validate the slope stability analysis, slope stability analysis simulation with homogeneous clay soil, medium homogeneousclay and homogeneous rigid clay with mast strengthening and evaluation of slope stability analysis in the study case. Theresults of the numerical analysis based on the influence of the pile position on the slope, pile diameter, pile length, and spacingbetween the piles with two pile head conditions is free head and fixed head, the condition of the mast is sufficient to improvethe safety factor of slope stability.